2014
DOI: 10.2147/rrtm.s53984
|View full text |Cite
|
Sign up to set email alerts
|

Public perception of climate change and its impact on health and environment in rural southwestern Nigeria

Abstract: Background: Climate change (CC) has received extensive media attention recently, and it is currently on the international public health agenda. A study of knowledge and attitudes to climate change, most especially from rural Nigerian communities, is important for developing adaptation strategies. This is a study of public perceptions of CC and its impact on health and environment in rural southwestern Nigeria. Methods: This was a community-based descriptive cross-sectional study of 1,019 rural respondents usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 11 publications
4
6
2
Order By: Relevance
“…The other less scientific reasons given by the participants, such as black smoke of vehicles, could be due to their low level of education and less exposure to the scientific facts by virtue of their occupation. These results also supported by other studies carried out in Bangladesh and other LDCs such as Nigeria and small island countries such as Trinidad and Tobago [ 30 , 37 ].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The other less scientific reasons given by the participants, such as black smoke of vehicles, could be due to their low level of education and less exposure to the scientific facts by virtue of their occupation. These results also supported by other studies carried out in Bangladesh and other LDCs such as Nigeria and small island countries such as Trinidad and Tobago [ 30 , 37 ].…”
Section: Discussionsupporting
confidence: 88%
“…Almost 46 % of the vulnerable community had not heard about CC, which might be a concern for the policy makers in health sector to provide adequate community level training on CC and its impact on health through the community clinics. The results are similar in two other studies conducted in LDCs, Nigeria [ 30 ] and Nepal [ 35 ], where 54 % and 51.3 %, respectively, of the participants reported they know about ‘climate change’. From our study, of those who had knowledge about CC, the majority named mass media (television, radio, newspaper etc.)…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A small number of 19% (76) of the respondents reported not having heard about climate change. These results agree with other studies conducted in Nigeria, Asekun-Olarinmoye et al (2014) [29] and Banstola et al (2013) [30], where 54 % and 51.3 %, respectively, of the participants reported they knew about 'climate change'. The findings also concur with those of Abedin et al (2019) [31], who found that, ''Climate change is a familiar term to the local people in Southwestern Coastal Bangladesh''.…”
Section: Community Knowledge and Perception Of Climate Change In Nzoia River Basinsupporting
confidence: 92%
“…Our study is the first large-scale quantitative attempt to assess the impact of climate change on health of the vulnerable communities in Bangladesh ( 27 ). Similar studies have been conducted in Philippines ( 28 ), Vietnam ( 29 ), the United States of America, Canada, Malta ( 30 ), Nigeria ( 31 ), Nepal ( 32 ), India ( 33 ), Australia ( 34 ), and China ( 35 ), although their main focus was on people's perception about the impact of climate change on health. A cross-sectional study of two villages in Bangladesh had some limitations with regard to generalizability but their findings on climate-related health coping supports some of the findings of our study ( 26 ).…”
Section: Discussionmentioning
confidence: 67%